First observation of the decay B(c)+ → J/ψπ(+) π- π+. - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (American Physical Society, 2012)
The decay B(c)(+) → J/ψπ(+) π(-) π(+) is observed for the first time, using 0.8 fb(-1) of pp collisions at sqrt[s] = 7 TeV collected by the LHCb experiment. The ratio of branching fractions B(B(c)(+) → J/ψπ(+) π(-) π(+))/B(B(c)(+)→J/ψπ^{+}) is measured to be 2.41 ± 0.30 ± 0.33, where the first uncertainty is statistical and the second is systematic. The result is in agreement with theoretical predictions.